Therapeutic Approaches of Dual-targeted Nanomedicines for Tumor Multidrug Resistance - Han, Weili; Shen, Zhenglin; Zou, Jie; Ye, Qiufang; Ge, Cheng; Zhao, Yuqin; Wang, Ting; Chen, Yafang (Current Drug Delivery, 2024)
Currently, the main cause of cancer chemotherapy failure is multi-drug resistance (MDR), which involves a variety of complex mechanisms. Compared with traditional small-molecule chemotherapy, targeted nanomedicines offer promising alternative strategies as an emerging form of therapy, especially active targeted nanomedicines. However, although single-targeted nanomedicines have made some progress in tumor therapy, the complexity of tumor microenvironment and tumor heterogeneity limits their efficacy. Dual-targeted nanomedicines can simultaneously target two tumor-specific factors that cause tumor MDR, which have the potential in overcoming tumor MDR superior to single-targeted nanomedicines by further enhancing cell uptake and cytotoxicity in new forms, as well as the effectiveness of tumor-targeted delivery. This review discusses tumor MDR mechanisms and the latest achievements applied to dual-targeted nanomedicines in tumor MDR.
Keywords: Dual-targeted nanomedicines